THE DIFFERENCES IN COOL PACK COMPRESSES AND DEEP BREATH RELAXATION TECHNIQUE ON PAIN IN SCHOOL-AGED CHILDREN AFTER THE BOOSTER Td - Martina Sulasmiati; Chr. Asri Endah Nuratri (Jurnal Kesehatan, 2020)
Pain is an uncomfortable feeling and a major source of distress for children. Pain due to invasive action (immunization) can be reduced by applying the principle of atraumatic care. Cool pack compresses and deep relaxation techniques can be used to reduce pain, which is a non-pharmacological method. This study aims to identify the effectiveness of cool pack compresses and relaxation techniques of deep breaths on pain in school-age children after Td booster immunization. This study's design used a quasi-experimental post-test only a nonequivalent control group; the research instrument used a VAS (Visual Analog Scale) scale with 34 school-age children as respondents, divided into two groups, namely the cool pack group and 17 deep breath relaxation techniques. Respondents using a simple random sampling technique. The study results based on the Mann-Whitney statistical test showed no difference in the level of pain between the cool pack compress and the deep breathing relaxation technique. The value ƿ = 0.375 > α = 0.05. Researchers suggest that there is assistance from their parents or their closest family in the immunization action for school-age children. Support and attention can distract from pain and comfort the child.